Recombinant enzymes-- from basic science to commercialization - Amid, Azura (Springer, 2015)
This edited work presents studies that clarify the basics of producing recombinant enzymes that finally lead to commercialization. It enables researchers to see what is crucial to the commercialization process, from examining the cloning method, using analytical techniques such as calculating the total protein content and enzyme activity, through considering upstream and downstream processes, to the final product.℗l Readers will discover the importance of the cloning method as it influences the upstream and downstream processes and determines the level of success of the recombinant enzyme commercialization processes. We see that the two main factors that are particularly sensitive during the cloning process are the vector and the host.℗l A discussion of analytical techniques is presented followed by studies on important stages during the upstream processes including the process of optimizing the media to get results and high enzyme activity. Downstream processes such as the cell disruption technique, purification and formulation of the final product are then considered. The reader is introduced to software that helps streamline recombinant enzyme production from the upstream to downstream processes, to facilitate the process of up-scaling production.℗l This work includes a case study as tool, to guide understanding of the commercialization process. The work is written for researchers in the field and is especially suited to those who are under pressure to embark on the tough process of commercialization.℗l